Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
a) f(x) = (x-4)(x+8)= x²+8x-4x-32 = x² + 4x - 32
m. zerowe: x=4, x=-8
b) f(x)= 3(x+1)²= 3(x²+2x+1)= 3x² + 6x + 3
m. zerowe: x = -1
Odpowiedź:
a) y = (x - 4) (x + 8)
y=x^2+8x-4x-32
y=x^2+4x-32 wzór ogólny
x^2+4x-32=0
a=1 b=4 c=-32
∆=(4)^2-4*1*(-32)=16+128=144
∆>0
Są dwa pierwiastki (miejsca zerowe)
√∆=√144=12
x1=(-4-12)/2=-16/2=-8
x2=(-4+12)/2=8/2=4
Miejsca zerowe to
x=-8
x=4
e) y = 3 (x+1)²
y=3(x^2+2x+1)
y=3x^2+6x+3 wzór ogólny
a=3 b=6 c=3
∆=6^2-4*3*3=36-36=0
∆=0 jest jeden pierwiastek podwójny
x0=-6/6=-1
Miejsce zerowe x=-1
Szczegółowe wyjaśnienie: